Since

f(x)=x+b and

f(6)=7, substituting

6 for

x in

f(x)=x+b gives

f(6)(6)+b=7. Then, solving the equation

(6)+b=7 for b gives

+b=7, or

9+b=7. Thus,

b=7−9=−2. Substituting this value back into the original function gives

f(x)=x−2; therefore, one can evaluate

f(−2) by substituting

−2 for

x:(−2)−2=−−2=−3−2=−5Choice B is incorrect as it is the value of b, not of f(−2). Choice C is incorrect as it is the value of

f(2), not of

f(−2). Choice D is incorrect as it is the value of

f(6), not of

f(−2).